Allosteric Regulation of HIV-1 Capsid Structure for Gag Assembly, Virion Production, and Viral Infectivity by a Disordered Interdomain Linker - Koma, Takaaki; Kotani, Osamu; Miyakawa, Kei; Ryo, Akihide; Yokoyama, Masaru; Doi, Naoya; Adachi, Akio; Sato, Hironori; Nomaguchi, Masako (Journal of virology, 2019)
HIV-1 particle production and infection are highly ordered processes. Viral Gag proteins play a central role in the assembly and disassembly of viral molecules. Of these, capsid protein (CA) is a major contributor to the Gag-Gag interactions. CA consists of two structured domains, i.e., N-terminal (NTD) and C-terminal (CTD) domains, connected by an unstructured domain named the interdomain linker. While multiple regions in the NTD and CTD are reported to play roles in virion morphogenesis and infectivity, the roles of the linker region in Gag assembly and virus particle formation remain elusive. In this study, we showed by biological and molecular analyses that the linker region functions as an intramolecular modulator to tune Gag assembly, virion production, and viral infectivity. Our study thus illustrates a hitherto-unrecognized mechanism, an allosteric regulation of CA structure by the disordered protein element, for HIV-1 replication. The retroviral Gag capsid (Gag-CA) interdomain linker is an unstructured peptide segment connecting structured N-terminal and C-terminal domains. Although the region is reported to play roles in virion morphogenesis and infectivity, underlying molecular mechanisms remain unexplored. To address this issue, we determined biological and molecular phenotypes of HIV-1 CA linker mutants by experimental and in silico approaches. Among the nine linker mutants tested, eight exhibited attenuation of viral particle production to various extents mostly in parallel with a reduction in viral infectivity. Sucrose density gradient, confocal microscopy, and live-cell protein interaction analyses indicated that the defect is accompanied by attenuation of Gag-Gag interactions following Gag plasma membrane targeting in the cells. In silico analyses revealed distinct distributions of interaction-prone hydrophobic patches between immature and mature CA proteins. Molecular dynamics simulations predicted that the linker mutations can allosterically alter structural fluctuations, including the interaction surfaces apart from the mutation sites in both the immature and mature CA proteins. These results suggest that the HIV-1 CA interdomain linker is a cis -modulator of the CA interaction surfaces to optimize efficiency of Gag assembly, virion production, and viral infectivity. IMPORTANCE HIV-1 particle production and infection are highly ordered processes. Viral Gag proteins play a central role in the assembly and disassembly of viral molecules. Of these, capsid protein (CA) is a major contributor to the Gag-Gag interactions. CA consists of two structured domains, i.e., N-terminal (NTD) and C-terminal (CTD) domains, connected by an unstructured domain named the interdomain linker. While multiple regions in the NTD and CTD are reported to play roles in virion morphogenesis and infectivity, the roles of the linker region in Gag assembly and virus particle formation remain elusive. In this study, we showed by biological and molecular analyses that the linker region functions as an intramolecular modulator to tune Gag assembly, virion production, and viral infectivity. Our study thus illustrates a hitherto-unrecognized mechanism, an allosteric regulation of CA structure by the disordered protein element, for HIV-1 replication.